Post-treatment of municipal wastewater using microalgae and activated sludge synergy - James, Abraham Olamilekan [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The problem of untreated and inadequately treated wastewater still persists globally. This has not only contributed to the increasing environmental pollution loads, but has also failed to harness the bioeconomy materials present in wastewater. While the science of microalgae-based treatment technology has shown to be efficient for treatment and recovery of potential resource, the majority of the studies were conducted under controlled conditions. Therefore, this present study evaluated the performance of native microalgae-activated sludge (MAS) growth for tertiary treatment of anaerobically digested wastewater from an upflow anaerobic sludge blanket (UASB) in an outdoor lab-scale photobioreactors (2 L). Seven different conditions with distinct inoculum proportions (Conditions: 1 to 3 is MAS; 4 to 6 is microalgae controls; 7 is without inoculum) were operated in batch mode reactor in triplicate for 5-days of hydraulic retention time (HRT) at 11.5:12.5 Photo-hours, to identify the best inoculum proportion for adopted in pilot flat panel photobioreactor. Condition 1 (0.10gL-1: microalgae and 0.20gL-1: activated-sludge), with lowest MAS proportion showed the best outcome with cell density productivity (2.03 x 107 cells.mL-1) along with biomass of 0.13 g TSS.L-1.d-1 and the total phosphorus uptake (85.07%), total nitrogen uptake (66.14%), logarithmic removal (Log-Re) of bacterial pathogens (water quality indicators), which showed Log-Re (3.3 for total coliforms (137E+02 CFU.100 mL-1) and 4.7 for Escherichia coli (0.00E+00 CFU.100 mL-1)). The best performing MAS (condition 1) was tested in a pilot flat panel photobioreactor, alongside a control, inoculated with the microalgae proportion of the MAS, and operated under 5-days and 3-days HRT. The performance of the system was determined by the efficiency of nutrient removal and recovery, biomass sedimentation and removal of Escherichia coli and Total Coliforms. Results showed that high HRT favoured the performance of MAS with respect to biomass growth, with significantly higher (p < 0.05) removal efficiency, 88.0, 79.0, 59.5% for total phosphorus (TDP), ammonium nitrogen (NH+4-N), chemical oxygen demand (CODfiltered), respectively at 5 days HRT. The average biomass productivity and growth rate for HRTs 5 days and 3 days are 59.41±12.31 mg TSS L-1 d-1, 0.08±0.01 d-1 and 25.56±11.09 mg TSS L-1 d-1, 0.03±0.01 d-1, respectively. The log-Re > 4.0 CFUmL-1 and > 3.5 CFUmL-1 were achieved for E. coli and total coliforms, respectively at both HRTs, and showed the potential for agricultural use for complying with the WHO recommended standard of 103 MPN.100mL-1. Overall, results showed a promising feasibility of outdoor microalgae-based treatment of wastewater cost effectively. However, self-settling efficiency was conversely low 33.0 and 14.0% for HRTs 5 days and 3 days, respectively, and suspiciously impacted by high pH (> 10.0) on bacterial population and the dominance of non-mucilage Cyanobium sp. (98%).

O problema das águas residuárias não tratadas ou tratadas inadequadamente ainda persiste globalmente. Isso não tem apenas contribuído para o aumento das cargas de poluição ambiental, mas também falhado em aproveitar os materiais bioeconômicos presentes nas águas residuárias. Embora a ciência da tecnologia de tratamento baseada em microalgas tenha se mostrado eficiente para o tratamento e recuperação de recursos potenciais, a maioria dos estudos foi realizada sob condições controladas. Portanto, o presente estudo avaliou o desempenho do crescimento de microalgas nativas-lodo ativado (MLA) para o tratamento terciário de águas residuárias digeridas anaerobiamente em um reator anaeróbio de fluxo ascendente com manta de lodo (UASB), a partir de fotobiorreatores externos em escala laboratorial (2 L). Sete diferentes condições com proporções distintas de inóculo (Condições: 1 a 3 é MLA; 4 a 6 são controles de microalgas; 7 é sem inóculo) foram operadas em bateladas em reator em triplicata, com tempo de retenção hidráulica (TRH) de 5 dias em 11,5:12,5 Foto-horas, para identificar a melhor proporção de inóculo a ser adotada no fotobiorreator piloto do tipo flat planel. A condição 1 (0,10 g.L -1 : microalga e 0,20 g.L -1 : lodo ativado), com menor proporção de MLA, apresentou o melhor resultado, com produtividade de densidade celular (2,03 x 107 células.mL-1 ) juntamente com biomassa de 0,13 g SST.L-1 .d-1 , remoção de fósforo total (85,07%) e nitrogênio total (66,14%) e remoção logarítmica (Log-Re) de bactérias patogênicas (indicadores de qualidade da água), com LogRe 3,3 para coliformes totais (137E+02 UFC.100 mL-1 ) e 4,7 para Escherichia coli (0,00E+00 UFC.100 mL1 ). O MLA de melhor desempenho (condição 1) foi testado em um fotobiorreator piloto do tipo flat planel, ao lado de um controle inoculado com a proporção de microalgas do MLA e operado sob TDH de 5 e 3 dias. O desempenho do sistema foi determinado pela eficiência de remoção e recuperação de nutrientes, sedimentação da biomassa e remoção de Escherichia coli e coliformes totais. Os resultados mostraram que o TRH mais alto (5 dias) favoreceu o desempenho do MLA em relação ao crescimento da biomassa, com eficiência de remoção significativamente maior (p < 0,05), 88,0; 79,0; 59,5% para fósforo dissolvido total (FDT), nitrogênio amoniacal (NH+ 4-N) e demanda química de oxigênio (DQOfiltrado), respectivamente. A produtividade média de biomassa e taxa de crescimento para TRHs de 5 e 3 dias foi de 59,41±12,31 mg SST.L -1 .d -1 , 0,08±0,01 d-1 e ii 925,56±11,09 mg SST.L -1 .d -1 , 0,03±0,01 d-1 , respectivamente. Os Log-Re > 4,0 UFCmL-1 e > 3,5 UFCmL-1 foram obtidos para E. coli e coliformes totais, respectivamente, em ambos os TRHs, e mostraram potencial para uso agrícola por atender ao padrão recomendado pela Organização Mundial da Saúde (OMS) de 103 MPN.100mL-1 . No geral, os resultados mostraram uma viabilidade economicamente promissora do tratamento de águas residuárias à base de microalgas ao ar livre. No entanto, a eficiência de autofixação foi inversamente baixa de 33,0 e 14,0% para TRHs de 5 e 3 dias, respectivamente, e supostamente impactada pelo alto pH (> 10,0) na população bacteriana e pela dominância da não-mucilagem Cyanobium sp. (98%).
Pós-tratamento de efluentes municipais utilizando sinergia de microalgas e lodo ativado
Keywords: Microalgae-activated sludge; Nutrient recovery; Pollutant removal; Bioflocculation; Hydraulic retention time